The mathematical models and function algorithms of automatic control system of dynamic treatment process on underground massive - Pavlysh, V.N.; Lazebnaya, L.A. (Искусственный интеллект, 2014)
The mathematical models of technological process of pneumatic and hydrodynamic treatment on anisotropic
underground rock massive, saturated with useful minerals, is considered. The treatment applies as a way of
directed changing of massive status for intensification of mineral extraction and its effectiveness depends of
quality of parameters control. The structure of the automatic control system and the algorithm of its
parameters selection is proposed. Розглянуто математичні моделі технологічного процесу пневматичної та гідродинамічної дії на анізотропні
підземні породні масиви, насичені корисною мінеральною сировиною. Дія здійснюється як спосіб
спрямованої зміни стану масиву з метою інтенсифікації вилучення сировини. Запропоновано структуру
системи автоматизованого керування та алгоритми контролю її параметрів. Рассматриваются математические модели технологического процесса пневматического и гидродинамического воздействия на анизотропные подземные породные массивы, насыщенные полезным
минеральным сырьем. Воздействие осуществляется как способ направленного изменения состояния массива
с целью интенсификации извлечения сырья. Предложена структура системы автоматизированного
управления и алгоритмы контроля ее параметров.